Improvement of the method used for control of starting direkt-currentrailway motor - Андрійченко, Володимир Павлович; Закурдай, Світлана Олександрівна; Костенко, Іван Олександрович (Eastern-European Journal of Enterprise Technologies, 2014)
The analysis of methods for rotation speed control of direct-current traction motors with the series and compound excitation is conducted in the paper. The scheme to improve energy efficiency of speed control devices of traction electric motors of public electric transport rolling stock is proposed. The proposed scheme using the increasing DC-DC converter allows to perform a smooth TEM field weakening, improve the shunt coil copper use and reduce electric power consumption at starting the rolling stock. In this case, weakening the compound excitation TEM field is conducted by changing the current in both series, due to the input converter circuit, and shunt coil. Moreover, current control in the shunt coil, the magnetizing force of which is directed opposite the magnetizing force of the series coil, is performed due to the output converter circuit. The electrical schematic diagram of the test stand and results of studying the proposed field weakening method are proposed.